2008
DOI: 10.1002/jcop.20266
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood social processes and academic achievement in elementary school

Abstract: To examine how neighborhood characteristics influence academic achievement, data were drawn from a community survey of low‐income neighborhoods and linked with data on performance on standardized testing for third‐grade students attending elementary schools in those communities. Results of multilevel logistic regressions indicated that probability of passing the reading portion of the test was associated with high neighborhood expectations for educational attainment and high collective socialization. Contrary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 41 publications
1
18
0
1
Order By: Relevance
“…In many studies, the two concepts have been theoretically and operationally integrated into the collective efficacy concept, which highlights both the social bonding and collective functioning of geographically bounded communities (Sampson et al, 1997). In fact, collective efficacy has been linked to a host of important outcomes, such as youth violence (Morenoff, Sampson, & Raudenbush, 2001;Sampson et al, 2005), adolescent development (Browning, Burrington, Leventhal, & Brooks-Gunn, 2008;Emory, Caughy, Harris, & Franzini, 2008), and adult mortality (Wen et al, 2005). However, the current study shows that perhaps, under some circumstances, the two key components of collective efficacy should be separately examined because they may have different impacts on the outcome of interest.…”
Section: Discussionmentioning
confidence: 99%
“…In many studies, the two concepts have been theoretically and operationally integrated into the collective efficacy concept, which highlights both the social bonding and collective functioning of geographically bounded communities (Sampson et al, 1997). In fact, collective efficacy has been linked to a host of important outcomes, such as youth violence (Morenoff, Sampson, & Raudenbush, 2001;Sampson et al, 2005), adolescent development (Browning, Burrington, Leventhal, & Brooks-Gunn, 2008;Emory, Caughy, Harris, & Franzini, 2008), and adult mortality (Wen et al, 2005). However, the current study shows that perhaps, under some circumstances, the two key components of collective efficacy should be separately examined because they may have different impacts on the outcome of interest.…”
Section: Discussionmentioning
confidence: 99%
“…physical and social characteristics of neighborhoods influence health and morbidity (Cohen et al 2003;Cubbin et al 2008), children's safety (Dowswell and Tanner 2002;McDonell and Skosireva 2009); educational attainment (Emory et al 2008;McWayne et al 2007), parenting practices (Kotchick and Forehand 2002;McDonell 2007), and child maltreatment ), among other indicators. Indeed, the social attachments fostered through a sense of community are central to individual and family well-being and contribute to neighborhood vibrancy (Manzo and Perkins 2006).…”
mentioning
confidence: 98%
“…Additionally, macro-level indicators, particularly decennial census data, are often outdated at the point they are used to characterize the neighborhood. Further, administrative data may not be designed for use in assessing neighborhood effects (Emory et al 2008), leading researchers to inferences that may not be tenable.…”
mentioning
confidence: 98%
“…Brody and colleagues (2001) found that collective socialization moderated the relationship between neighborhood disadvantage and affiliation with deviant peers: the relationship was weaker in the presence of higher socialization. In other work children’s reading achievement was associated with high neighborhood expectations for educational attainment and high collective socialization (Emory, Caughy, Harris, & Franzini, 2008). Families in neighborhoods characterized by higher trust between neighbors were more likely to select child care homes and less likely to use exclusive parental care or relatives (Burchinal et al, 2008a).…”
Section: Literature Reviewmentioning
confidence: 97%